Environmental sustainability in Bangladesh and initiative and impact of Coats Bangladesh to ensure sustainable development - Zahir, Tonmoy (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2023.